Manajemen Humas dan Kepemimpinan Waka Humas di SMK Shofa Marwa - M Haikal Ardani; Meli Farah Nabila; Lia Anisyarifah; Marsya Syauban Nabila; Rofiq Hidayat (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to analyze public relations (PR) management practices and the leadership style of the Vice Principal for Public Relations (Waka Humas) in building a positive school image and establishing partnerships with industry sectors. The focus of the research lies in communication strategies, coordination patterns, and leadership approaches implemented to support school development programs based on industry collaboration. This research employs a qualitative approach using a case study method, with data collected through in-depth interviews, observations, and documentation analysis. The findings reveal that the Vice Principal for Public Relations applies strategic PR planning, including situation analysis, goal formulation, program implementation, and evaluation processes. Furthermore, a transformational leadership style is predominantly applied, characterized by the ability to motivate, inspire teachers and staff, and foster a collaborative culture in achieving school goals. This leadership approach has been proven effective in increasing stakeholder participation, expanding industrial networks, and strengthening the school’s image as an adaptive institution responsive to the needs of the workforce. Nevertheless, the study also identifies challenges related to limited resources, particularly concerning infrastructure support and time allocation for program implementation. These findings highlight the importance of enhancing the capacity of school public relations roles to ensure sustainable industrial partnerships and a strong institutional reputation.